The effects of acupoint catgut embedding therapy on anthropometric parameters and endocrine function in obese women: a systematic review and meta-analysis - Li, Shuangqiu; Zhou, Hongfei; Zhou, Muhan; Lou, Liangliang; Luo, Li; Ji, Shan (Frontiers in Nutrition, 2025)
PurposeThis study aimed to assess the effect of acupoint catgut embedding therapy (ACET) on anthropometric parameters and endocrine function in obese women through a systematic review and meta-analysis.MethodsA comprehensive search was conducted across international and Chinese databases [CNKI, Wanfang, Weipu, Sinomed, PubMed, Embase, Cochrane Library, Web of Science (WOS), and Scopus]. The search terms included “female,” “women,” “catgut implantation at acupoint,” “catgut embedding,” “acupoint embedding therapy,” “obesity,” “adiposity,” and “body weight,” etc. Studies included in this analysis were randomized controlled trials (RCTs) assessing the effects of ACET on obesity indicators such as body mass index (BMI), waist-to-hip ratio (WHR), lipid profiles such as triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL), and hormone levels such as luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone (T), and estradiol (E2). We used ROB 2.0 to assess the risk of bias. Data was analyzed using weighted mean differences (WMD) and risk ratios (RR) to measure effect sizes, and heterogeneity was assessed using I2 statistics. Conduct sensitivity analysis, publication bias testing, and subgroup analysis on indicators with high heterogeneity to explore the sources of heterogeneity.ResultsTwenty-three studies involving over 2,000 obese women were included. Risk of bias assessment revealed generally low bias in randomization and measurement domains, though selective reporting and missing data handling raised concerns in some studies. ACET significantly reduced BMI [−1.72 (95% CI: −2.13, −1.31)] and WHR [WMD −0.016 (95% CI: −0.034, 0.001)], with high heterogeneity in BMI analysis (I2 = 92.3%). Subgroup analyses suggested that heterogeneity decreased in different control groups and different treatment courses, such as diet guidance (I2 = 0.0%) and 12-week treatment duration (I2 = 32.9%). Publication bias assessments (Begg's and Egger's tests) indicated no significant bias for most indicators. However, the clinical efficacy rate showed potential publication bias upon trim-and-fill adjustment, though the effect remained significant. ACET significantly reduced TG and TC but not HDL, LDL, or insulin resistance. Hormonal changes included decreased LH and FSH and increased E2.ConclusionOur meta-analysis demonstrates that ACET significantly improves anthropometric parameters and endocrine function in obese women, though it does not significantly impact lipid metabolism or insulin resistance. The therapy's influence on female hormones may contribute to its efficacy in obesity treatment, highlighting the need for further studies to explore long-term effects and mechanisms.Systematic review registrationPROSPERO, identifier: CRD42025640157.